2005
DOI: 10.1074/jbc.m414045200
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of Galactose Sensitivity in UDP-Galactose 4′-Epimerase-impaired Mammalian Cells

Abstract: UDP-galactose 4-epimerase (GALE) catalyzes the final step in the Leloir pathway of galactose metabolism, interconverting UDP-galactose and UDP-glucose. Unlike its Escherichia coli counterpart, mammalian GALE also interconverts UDP-N-acetylgalactosamine and UDP-N-acetylglucosamine. Considering the key roles played by all four of these UDP-sugars in glycosylation, human GALE therefore not only contributes to the Leloir pathway, but also functions as a gatekeeper overseeing the ratios of important substrate pools… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 37 publications
(51 reference statements)
7
39
0
Order By: Relevance
“…Prior studies have demonstrated that GALE-impaired yeast (Douglas and Hawthorne, 1964;Ross et al, 2004), mammalian tissue culture cells (Schulz et al, 2005) and patients (Openo et al, 2006) all accumulate elevated levels of gal-1P upon exposure to high levels of environmental galactose, ostensibly because, when GALE is deficient, GALT activity is compromised by an accumulation of product (UDP-gal) and a depletion of substrate (UDP-glc).…”
Section: Loss Of Gale Results In Abnormal Accumulation Of Gal-1pmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have demonstrated that GALE-impaired yeast (Douglas and Hawthorne, 1964;Ross et al, 2004), mammalian tissue culture cells (Schulz et al, 2005) and patients (Openo et al, 2006) all accumulate elevated levels of gal-1P upon exposure to high levels of environmental galactose, ostensibly because, when GALE is deficient, GALT activity is compromised by an accumulation of product (UDP-gal) and a depletion of substrate (UDP-glc).…”
Section: Loss Of Gale Results In Abnormal Accumulation Of Gal-1pmentioning
confidence: 99%
“…GALE-deficient yeast are viable and apparently healthy, although they arrest growth upon exposure to even trace levels of environmental galactose (Douglas and Hawthorne, 1964;Ross et al, 2004). GALE-deficient Chinese hamster ovary (CHO) cells [ldlD cells (Krieger et al, 1989)] also demonstrate galactose-sensitive growth arrest, as well as defects in both N-and O-linked glycosylation (Kingsley et al, 1986;Schulz et al, 2005). Nonetheless, the relationship between yeast or tissue culture outcomes and the pathophysiology of epimerase deficiency galactosemia remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This is because (i) human cells have salvage pathways for UDP-Galp biosynthesis (indeed, Gal-1-P and UDP-Galp accumulate in GalE null mammalian cells [103]) and (ii) although defects in human GalE lead to type III galactosemia (114), inhibition of human GalE over a period of days may be tolerable. In any case, three lines of evidence suggest that some selectivity against trypanosome GalE enzymes should be possible.…”
Section: Cruzi) Gdp-man Is Also the Precursor Of Gdp-fuc (See Below)mentioning
confidence: 99%
“…After 2 min incubation, 100 l of 500 mM KH 2 PO 4 was added to the reaction mixture to stop the reaction. The final product, UDP-GlcNAc or UDP-N-acetyl-D-galactosamine (UDP-GalNAc), was measured and quantified mainly according to the method described by Schulz et al (24). In this method, the elution positions for UDP-GlcNAc and UDPGalNAc showed individual peaks.…”
mentioning
confidence: 99%